Kajian Keberadaan Ojek Sebagai Angkutan Umum Paratransit di Kota Semarang (Studi Kasus: Koridor Jalan Kesatrian, Jalan Ngesrep Timur V dan Jalan Karangrejo Raya) - Pratiwi, Ratna; Haryanto, Ragil (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
The existence of â€œOjeksâ€ along Kesatrian Jatingaleh, Ngesrep Timur V Sumurboto and Karangrejo Raya Srondol Wetan are driven by the lack of public transport services in meeting the needs of people movement around those corridors. Due to publicâ€™s high interest on using â€œOjeksâ€, then the existence of â€œOjeksâ€ become increasing and wide spreading characterized by the presence of â€œOjeksâ€ associations which locations are often considered unsuited and even interfere the traffic. Therefore, the purpose of this study was to assess the presence of â€œOjeksâ€ as public transport which are currently growing so as not to cause traffic chaos and to achieve better transportation development in the future. This study employed a mix of quantitative and qualitative methodology. â€œOjeksâ€ operators respondents are determined by census method, while for purposive and incidental sampling technique are used to determine the sample of â€œOjeksâ€ association chairman and key persons which are government/academia and â€œOjeksâ€ users. Descriptive analysis was used as the analysis technique, which then verified for its validity by triangulation approach. The analysis showed that the presence of â€œOjeksâ€ will always be needed as the gap filler against the public transport services. â€œOjeksâ€ become main livelihood so as to meet the economic needs on the one hand. On the other or social needs, establishment of â€œOjeksâ€ associations serve to accommodate the aspirations and information among â€œOjeksâ€members.